Pengaruh Disiplin Kerja, Lingkungan Kerja dan Pelatihan Kerja Terhadap Kinerja Karyawan NM Eyelashes Purbalingga - Adam, Duki Adam (Awatara Publisher, 2025)
NM Eyelashes Purbalingga in 2023 there will still be problems related to employee performance, from interviews and pre-research data, problems of low work discipline were found as indicated by high levels of tardiness and absenteeism, as well as less than optimal work environments and uneven job training. This research aims to analyze the influence of work discipline, work environment, and work training on employee performance. Using quantitative descriptive methods with the help of SPSS version 26.0, this research involved 36 employees with a saturated sampling technique. The research results show that partially work discipline, work environment, and work training each have a positive and significant influence on employee performance. Simultaneously, these three variables contribute to employee performance with a coefficient of determination of 54.8%, so 45.2% is influenced by other variables not studied. So companies are expected to apply sanctions for disciplinary violations, maintain a positive work environment, and provide equitable and sustainable training so that employee performance can improve and problems are resolved.